The IBEX Knowledge-Base: A central resource for multiplexed imaging techniques. - Andrea J Radtke; Ifeanyichukwu U Anidi; Leanne Arakkal; Armando J Arroyo-Mejias; Rebecca T Beuschel; Katy Börner; Colin J Chu; Beatrice Clark; Menna R Clatworthy; Jake Colautti; Fabian Coscia; Joshua Croteau; et al. (PLoS Biology, 2025)
Multiplexed imaging is a powerful approach in spatial biology, although it is complex, expensive and labor-intensive. Here, we present the IBEX Knowledge-Base, a central resource for reagents, protocols and more, to enhance knowledge sharing, optimization and innovation of spatial proteomics techniques.